A Fertilizer Monitoring System for Fertigation Using IoT Platform - Ishak, Hafiz; Ab Rahman, Tasiransurini (Evolution in Electrical and Electronic Engineering, 2025)
The Internet of Things (IoT) technology has revolutionized various sectors, including agriculture. By integrating IoT, sensors, and fertigation techniques, an intelligent system can be created, where the system will automate the fertigation process and adapt it dynamically based on environmental factors and plant needs. However, the uncontrol concentration value of fertilizer in fertigation planting systems becomes an issue. Thus, it is proposed to develop an automated fertilizer control for fertigation monitoring systems. This system controls the fertilizer and water supply using NodeMCU ESP32 microcontroller. A chilli paper plantation was used as a test plant where its temperature and moisture were monitored using NodeMCU ESP32 and Blynk application. The information received will be analyzed and uploaded to the Blynk platform. The result shows that the NodeMCU ESP32 is able to control the fertilizer and water supply, meanwhile, the user can monitor the temperature, moisture and water through the IoT platform that was displayed on Blynk application.